2020
DOI: 10.1371/journal.pone.0230918
|View full text |Cite
|
Sign up to set email alerts
|

Friends or foes? How activists and non-activists perceive and evaluate each other

Abstract: Little is known about how activists and non-activists perceive and evaluate each other. This is important because activists often depend on societal support to achieve their goals. We examined these perceptions and evaluations in three field experiments set in different contexts, i.e., student protests in the Netherlands 2014/2015 (Study 1, activist sample N = 190; Study 2, non-activist sample N = 145), and environmental protests in Paris in 2015 (Study 3, activist sample N = 112). Through a scenario method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Collective action scholars have traditionally argued that activists , that is, a social group within a wider society committed to particular ideological causes of injustice, constitute a driving force of any social movement. However, witnessing a rise in social justice movements across the globe made many collective action scholars recognize a crucial role of non‐activists , that is, members of the general public, in sustaining social justice causes to the extent that they legitimize demands of activists (see Jiménez‐Moya, Miranda, Drury, Saavedra, & González, 2019; Kutlaca, van Zomeren, & Epstude, 2020). Indeed, many social movements (e.g., Egypt's Arab Spring, Ukraine's Euromaidan) have been successful in influencing key decision‐makers in the respective countries to the extent that members of the larger public sustained civil resistance and became part of it (see Uluğ, Chayinska, & Tropp, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective action scholars have traditionally argued that activists , that is, a social group within a wider society committed to particular ideological causes of injustice, constitute a driving force of any social movement. However, witnessing a rise in social justice movements across the globe made many collective action scholars recognize a crucial role of non‐activists , that is, members of the general public, in sustaining social justice causes to the extent that they legitimize demands of activists (see Jiménez‐Moya, Miranda, Drury, Saavedra, & González, 2019; Kutlaca, van Zomeren, & Epstude, 2020). Indeed, many social movements (e.g., Egypt's Arab Spring, Ukraine's Euromaidan) have been successful in influencing key decision‐makers in the respective countries to the extent that members of the larger public sustained civil resistance and became part of it (see Uluğ, Chayinska, & Tropp, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, little research has systematically examined a potential variability and similarity in the associations between (a) moral outrage, (b) collective efficacy beliefs and (c) prosocial disobedience attitude in predicting commitment to a social justice cause and political participation among both activists and non‐activists. While it is largely recognized that a conjoint effort of both groups determines the success of social movements (e.g., Kutlaca et al, 2020; Simon & Klandermans, 2001), the current study aims to explicate both similarities and differences in how social‐psychological precursors relate to social identification with a cause and collective action intentions among activists and non‐activists. Before we move forward, there is one important theoretical proposition that our case study additionally seeks to examine.…”
Section: Introductionmentioning
confidence: 99%
“…A protocol was developed to standardize the data collection based on previous research conducted by the authors ( Ferris et al, 2019 ; Kutlaca et al, 2020b ) and other researchers ( Van Leeuwen et al, 2015 ; Walgrave et al, 2016 ). Research assistants were instructed to wear t-shirts or stickers on their coats that identified them as being from the university, and to carry their university ID card with them.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, it has been found that nonactivist peers hold positive stereotypes about collective action groups including viewing activists as being motivated, helpful, effective, and powerful (Stuart et al, 2018). In fact, recent work on how activists and nonactivists perceive and evaluate each other found that nonactivists demonstrated a positive view of their activist counterparts in regard to morality (Kutlaca, van Zomeren & Epstude, 2020).…”
Section: Stereotypes Of Activistsmentioning
confidence: 99%